Cost-effectiveness analysis of a postoperative 48-hour care bundle for high-risk patients undergoing abdominal surgery - Cleiton Pando; Ana Paula Etges; Miriam Z. Marcolino; Ricardo B. Cardoso; Adriene Stahlschmidt; Carise A. Polanczyk; Luciana C. Stefani (PLoS ONE, 2025)
Background Enhancing surgical care pathways, including scaling-up care after surgery, seeks to deliver better patient-centered care and improve outcomes. However, the value associated with these pathways need to be investigated. Methods We analyzed the potential increase in efficiency of a new care pathway, a postoperative 48-hour care bundle designed to enhance care for high-risk patients undergoing major abdominal surgery, based on micro-costing and cost-effectiveness analyses. Data from a prospective cohort of patients who underwent a high-risk surgical bundle were compared with those who received the standard care regimen. The bundle included standardized risk communication using the ex-care model, implementing a high-risk patient discharge checklist from the recovery room to the ward, ensuring prompt nursing admission to the ward, increasing the frequency of vital sign monitoring in the surgical ward, conducting troponin measurements, and providing rapid access to medical support when needed. Costs were calculated individually throughout the postoperative period until discharge following the time-driven activity-based costing method. One-year survival rates were evaluated using Kaplan-Meier survival curves. A cost-effectiveness analysis was conducted in terms of life-year gain (LYG) and incremental cost-effectiveness ratio (ICER). Results Data from 130 and 188 patients in the bundled and non-bundled groups, respectively, were evaluated. The mean cost per patient of the high-risk surgical bundle was US$2114.63 while for the conventional care group it was US$1447.86. The Kaplan-Meier curve for one-year mortality showed that the groups differed significantly (p =  0.002). According to the model, the new care strategy incremented 0.12 life-year gained at an incremental cost of $150.12. The projected incremental cost-effectiveness ratio for one year of life was $1217.66. Conclusion Our results suggest that implementing a high-risk surgical bundle can enhance healthcare delivery efficiency, making it a valuable and cost-effective strategy for high-level testing to create a more sustainable healthcare system.